Pengembangan Modul Praktikum Laju Reaksi Berorientasi Discovery Learning untuk Melatih Keterampilan Proses Sains Peserta Didik - Sri Rahayu, Rafikah; Jusniar, Jusniar; Anwar, Muhammad (Chemistry Education Review (CER), 2024)
This research is a development research, which aims to develop and produce a practical module of reaction rate oriented to discovery learning to train students' science process skills. The development model used in research refers to the ADDIE development model (analysis, design, develop, implementation, and evaluation). The data sources used to measure validity were two validators who assessed the media and practical module material. The practicality data sources were two observers who assessed the learning implementation, 21 students, and two chemistry teachers. Measuring the effectiveness of the practical module employed a science process skills test for 21 students. The field trial of this practical module was conducted at MA DDI Lil Banat Parepare. The results of the research reveal that the practical module is valid, practical, and effective. The module validity, both in terms of the media and material received a very valid category. The results of learning implementation is 97.66% which is in very good category. The teachers’ and students responses using the practical module are in very high category as well, so the practical module is stated as practical. The field trials on 21 students in grade XI MIPA obtained an overall average result of students' science process skills of 83.34 after using the practical module. The practical module developed is stated as effective if the overall average score of the students is 80. Thus, the practical module developed is effective in chemistry practical activities, especially reaction rate material.